Slumber volume 1 ebook - Smith, Tyler Burton (Slumber, 2022)
We all have nightmares. What if you could pay somebody to enter your dreams and shoot that nightmare in the goddamn face? That’s where Stetson comes in. She’s a nightmare hunter. A dream detective. She enters her clients’ dreams through a door, investigates their dreamscapes, and kills their nightmares. But Stetson’s past comes back to haunt her as she tracks down a nightmare serial killer responsible for the mysterious death of her daughter.